Use of high-density activation and voltage mapping in combination with entrainment to delineate gap-related atrial tachycardias post atrial fibrillation ablation. Issue 7 (10th January 2021) - Vlachos, Konstantinos; Efremidis, Michael; Derval, Nicolas; Martin, Claire A; Takigawa, Masateru; Bazoukis, George; Frontera, Antonio; Gkalapis, Charis; Duchateau, Josselin; Nakashima, Takashi; Letsas, Konstantinos P; Mililis, Panagiotis; et al.
Abstract: Aims: An incomplete understanding of the mechanism of atrial tachycardia (AT) is a major determinant of ablation failure. We systematically evaluated the mechanisms of AT using ultra-high-resolution mapping in a large cohort of patients. Methods and results: We included 107 consecutive patients (mean age: 65.7 ± 9.2 years, males: 81 patients) with documented endocardial gap-related AT after left atrial ablation for persistent atrial fibrillation (AF). We analysed the mechanism of 134 AT (94 macro-re-entries and 40 localized re-entries) using high-resolution activation mapping in combination with high-density voltage and entrainment mapping. Voltage in the conducting channels may be extremely low, even <0.1 mV (0.14 ± 0.095 mV, 51 of 134 AT, 41%), and almost always <0.5 mV (0.03–0.5 mV, 133 of 134 AT, 99.3%). The use of multipolar Orion, HDGrid, and Pentaray catheters improved our accuracy in delineating ultra-low-voltage areas critical for maintenance of the circuit of endocardial gap-related AT. Conventional ablation catheters often do not detect any signal (noise level) even using adequate contact force, and only multipolar catheters of small electrodes and shorter interelectrode space can detect clear fractionated low-amplitude and high frequency signals, critical for re-entry maintenance. We performed a diagnosis in 112 out of 134 AT (83.6%) using only activation mapping and in 134 out of 134 AT (100%) using the combination of activation and entrainment mapping. Conclusion : High-resolution activation mapping in combination with high-density voltage and entrainment mapping is the ideal strategy to delineate the critical part of the circuit in endocardial gap-related re-entrant AT after AF ablation.